2016
DOI: 10.1073/pnas.1524209113
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced actuating nanotransducers

Abstract: Nanoactuators and nanomachines have long been sought after, but key bottlenecks remain. Forces at submicrometer scales are weak and slow, control is hard to achieve, and power cannot be reliably supplied. Despite the increasing complexity of nanodevices such as DNA origami and molecular machines, rapid mechanical operations are not yet possible. Here, we bind temperatureresponsive polymers to charged Au nanoparticles, storing elastic energy that can be rapidly released under light control for repeatable isotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
149
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 35 publications
2
149
0
Order By: Relevance
“…This self-assembly process is accelerated through several cycles of heating and cooling, bringing PNIPAM to thermodynamic equilibration with the aqueous phase. 30 The resulting coated particles along with water are mixed with hexadecane through vigorous shaking and settle at the H 2 O/hexadecane interface (Fig. 1b and c) within 10 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This self-assembly process is accelerated through several cycles of heating and cooling, bringing PNIPAM to thermodynamic equilibration with the aqueous phase. 30 The resulting coated particles along with water are mixed with hexadecane through vigorous shaking and settle at the H 2 O/hexadecane interface (Fig. 1b and c) within 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…Separate measurements have shown the capability for switching such PNIPAM AuNP constructs on microsecond timescales. 30,39 …”
Section: Resultsmentioning
confidence: 99%
“…The actuating nanotransducers (ANTs), consist of thermo‐sensitive polymers—poly( N ‐isopropylacrylamide), abbreviated as pNIPAM—attached to plasmonic (gold) nanoparticles and dispersed in water. The plasmonic nanoparticles efficiently and quickly convert light into heat, triggering a strong response from the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…These studies lead us to conclude that the contradictory phenomena reported in the literature described above may be ascribed to the quality of thermoresponsive polymer passivation on the surface of the NP.When PNIPAM ligands are not strongly attached to the Au NP surface, [7,21,22] the partial dissociation of PNIPAM into the solution occurs and thus becomes free linear PNIPAM chains.T hey function as the physical crosslinkers to facilitate the aggregation of Au NPs when temperature increases above LCST,a nd correspondingly ar ed-shift of plasmonic absorption with decreased intensity and an on/off catalytic behavior are observed. In contrast, with as trong tethering of PNIPAM ligands on the Au NP surface [5,19,20] and the temperature rising over the LCST,only the collapse (i.e., shrinkage) of surface PNIPAM ligands occurs and thus no aggregation of Au NPs,h ence as maller red-shift of plasmonic absorption with increased intensity and an on-monotonic catalytic action are yielded.…”
Section: Introductionmentioning
confidence: 83%